Seasonal patterns and drivers of nitrogen fixation in soybeans - Luiz Felipe Almeida; Federico Gomez; Francisco Palmero; Gabriel Hintz; Adrian Correndo; Jeremy Ross; Mark Licht; Shaun Casteel; Manninder Singh; Seth Naeve; Rachel Vann; Jose Bais; et al. (European Journal of Agronomy, 2026)

Quantifying soybean biological nitrogen fixation using long-term isotope enrichment - Ophelia Tsai; Steven J. Hall; George L. Graef; Luis G. Posadas; James E. Specht; William G. Crumpton; Matthew J. Helmers; Shawn P. Conley (Plant and Soil, 2026)
Background and aims Biological nitrogen fixation (BNF) supplies much of soybean ( Glycine max (L.) Merr.) nitrogen (N) demand, but reported fixation rates vary widely, leading to uncertainty in the soybean N cycle. We quantified whole-plant soybean BNF and N allocation using long-term 15 N labeling to assess whether BNF can offset grain N removal in a high-yielding system, and to quantify root contributions to fixed N. Methods Field mesocosms in Iowa, USA received three legacy fertilizer N rates as 2 atom% 15 N-enriched urea for four prior seasons of maize ( Zea mays L.) production. In 2024, N-fixing and non-N-fixing soybeans were grown to physiological maturity. Grain, aboveground biomass, and roots were analyzed to quantify BNF and to estimate whole-plant N budget. Results Soybean derived 81.8% ± 1% (SE) of total plant N from BNF. Legacy N rate had no effect on whole-plant N accumulation, BNF, or N partitioning among tissues (p > 0.05). Roots contained ~2% of total fixed N, with most BNF-derived N allocated to grain. High grain N removal was largely offset by BNF (174.7 ± 8.9 kg N ha −1 ), resulting in a near-neutral partial N balance (−5.7 ± 2 kg N ha⁻ 1 ). Conclusion From this one-season mesocosm study, our finding of negligible fixed N in soybean roots indicates that neglecting root BNF does not necessarily bias conclusions about soybean N cycle. However, the combination of long-term isotope labeling and non-nodulating isolines yielded much less variable and higher BNF rates than previous studies, suggesting the possibility of underestimation for soybean BNF in historical studies.

Impacts of rotation, tillage, cover cropping, and drainage on soil health in soybean-based cropping systems: Evidence from 4–50-year trials across the US - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Chad D. Lee; David Jordan; Hanna J. Poffenbarger; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Agriculture, Ecosystems & Environment, 2026)

Commercial biostimulant seed treatments showed minimal impact on soybean seed yield across the United States - Fabiano Colet; Spyridon Mourtzinis; Rachel A. Vann; Seth Naeve; Shawn P. Conley; Emma G. Matcham; Andre Borja Reis; Hans Kandel; David Moseley; Michael Plumblee; Eros Francisco; Giovani Preza Fontes; et al. (Field Crops Research, 2025)

Soybean yield response to management practices (4–40 years) and soil health parameters - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Spyridon Mourtzinis; Chad D. Lee; David Jordan; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Field Crops Research, 2025)

How changes in cover crop termination timing affect soybean yield? A systematic review and meta-analysis - Camila Rebelatto Muniz; Tatiane Severo Silva; Camila Jorge Bernabé Ferreira; Shawn Conley; Spyridon Mourtzinis; Joe McClure; Seth Naeve; Rachel Vann; Matheus de Freitas Souza (Field Crops Research, 2025)

Assessing the influence of environmental drivers on soybean seed yield and nitrogen fixation estimates and uncertainties in the United States - Luiz Felipe Almeida; Adrian A. Correndo; Trevor Hefley; Gabriel Hintz; P.V. Vara Prasad; Mark Licht; Shaun Casteel; Maninder Singh; Seth Naeve; José Bais; Laura Lindsay; Shawn Conley; et al. (European Journal of Agronomy, 2025)

Cereal rye cover crop termination at or before soybean planting has minimal effect on soybean yield across the midwestern US - Tatiane Severo Silva; Spyridon Mourtzinis; Anthony Justin McMechan; Gabriela Inveninato Carmona; Bruce D. Potter; Kelley J. Tilmon; Louis S. Hesler; Nicholas J. Seiter; Robert Wright; Shannon L. Osborne; Thomas E. Hunt; Shawn P. Conley (Field Crops Research, 2024)

Filling the agronomic data gap through a minimum data collection approach - Fatima A.M. Tenorio; Juan I. Rattalino Edreira; Juan Pablo Monzon; Fernando Aramburu-Merlos; Achim Dobermann; Armelle Gruere; Juan Martin Brihet; Sofia Gayo; Shawn Conley; Spyridon Mourtzinis; Nester Mashingaidze; Alex Sananka; et al. (Field Crops Research, 2024)

Field-level yield benefits and risk effects of intensive soybean management across the US - Spyridon Mourtzinis; Paul Mitchell; Paul Esker; Anibal Cerrudo; Seth Naeve; Shawn Conley (Field Crops Research, 2023)

Linking soil health indicators to management history and soybean yield - Lindsay Chamberlain Malone; Matthew D. Ruark; Christopher J. Kucharik; Thea Whitman; Shawn P. Conley (Field Crops Research, 2023)

Soybean yield response to nitrogen and sulfur fertilization in the United States: contribution of soil N and N fixation processes - Luiz Felipe A. Almeida; Adrian Correndo; Jeremy Ross; Mark Licht; Shaun Casteel; Maninder Singh; Seth Naeve; Rachel Vann; Jose Bais; Hans Kandel; Laura Lindsey; Shawn Conley; et al. (European Journal of Agronomy, 2023)

On spline-based approaches to spatial linear regression for geostatistical data - Guilherme Ludwig; Jun Zhu; Perla Reyes; Chun-Shu Chen; Shawn P. Conley (Environmental and Ecological Statistics, 2020)

Assessing oocyte development and maturation in the threatened Delta Smelt, Hypomesus transpacificus - Tomofumi Kurobe; Micheal O. Park; Alireza Javidmehr; Foo-Ching Teh; Shawn C. Acuña; Cynthia J. Corbin; Alan J. Conley; William A. Bennett; Swee J. Teh (Environmental Biology of Fishes, 2016)

Effect of drought on Bradyrhizobium japonicum populations in Midwest soils - Coralie Barthelemy-Delaux; David Marburger; Pierre-Marc Delaux; Shawn Conley; Jean-Michel Ané (Plant and Soil, 2014)

Effect of cultivar, row spacing, and weed management on weed biomass, potato yield, and net crop value - Shawn P. Conley; Larry K. Binning; Timothy R. Connell (American Journal of Potato Research, 2001)